2021
DOI: 10.1038/s41598-021-97419-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation and subsurface damage formation in the ultrafine machining process of a diamond substrate through atomistic simulation

Abstract: This report explores the effects of machining depth, velocity, temperature, multi-machining, and grain size on the tribological properties of a diamond substrate. The results show that the appearance of graphite atoms can assist the machining process as it reduces the force. Moreover, the number of graphite atoms relies on the machining speed and substrate temperature improvement caused by the friction force. Besides, machining in a machined surface for multi-time is affected by its rough, amorphous, and defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It can be seen that when the depth changes from 7 Å to 10 Å, the increase in detached atoms is much greater than the previous three lower depths. These microscopic wear amounts can realize the transition from macro to micro in friction and wear experiments and can more intuitively investigate the micro-structure evolution of friction and wear [70].…”
Section: Indentation Depth and Its Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that when the depth changes from 7 Å to 10 Å, the increase in detached atoms is much greater than the previous three lower depths. These microscopic wear amounts can realize the transition from macro to micro in friction and wear experiments and can more intuitively investigate the micro-structure evolution of friction and wear [70].…”
Section: Indentation Depth and Its Effectsmentioning
confidence: 99%
“…The shear strain increases with the increase in temperature and has a cumulative effect, and the strain accumulation will accelerate diamond wear. According to relevant literature research [73,74], the increase of shear strain is attributed to the increase of friction heat during the friction process, which makes the temperature of the friction surface higher than the set temperature, and the carbon atoms and SiC ball at the friction interface will continue to react.…”
Section: Temperature and Its Effectsmentioning
confidence: 99%
“…Recently, the molecular dynamics (MD) simulation has been employed to investigate the machining and deformation mechanism of nano cutting process [33][34][35]. It provides a good insight into material behavior during the nanoscale cutting process, which is difficult to be observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the microscopic mechanisms of crack emergence and propagation in GaAs are not entirely understood and the contribution of the crack to deformation behavior is not yet clear. Additionally, studies of GaAs in plowing simulations have shown that the deformation process is always accompanied by the formation of dislocations, stacking faults and phase transformation [21,22]. The mechanical deformation response of GaAs to contact damage has attracted extensive attention [23].…”
Section: Introductionmentioning
confidence: 99%